Digital maintenance and the functional blocks for sustainable asset maintenance service – A case study - Bishal Raj Karki; Saru Basnet; Jinhua Xiang; Julian Montoya; Jari Porras (Digital Business, 2022)
Rapid advances in technology, data, and analytics have helped maintenance services to evolve from a mere reactive process to a fully digital solution. Digital maintenance services exhibit a variety of functionalities to every adopting industry, with monitoring, diagnosing, troubleshooting, predicting, and optimizing being the common influencer. The presence of digital maintenance is slowly growing in the asset-intensive industries; however, the early adopters have been benefitting the most. This research tries to showcase a digital and sustainable maintenance service approach from both a scientific study and a practice perspective. It explains essential blocks of digital maintenance from a proposed model and provides a basis for new and in-depth research in digitally enabled reliability. Using a case study approach, it further aims to validate a functionality model for digital and sustainable maintenance services; explains different blocks as digital offerings; highlights the importance of digitalization and digital maintenance, and presents the results achieved based on the implementation. Metso Outotec being one of the early adopters of digital maintenance, their Connected Service is studied as a case study from a practical perspective for this research. The outcome observes positive sustainable impacts such as economic savings, reduced production loss, time saved, reduced travel to the site, and ensuring safety through fault prevention.